Concomitant Polycythemia Vera and Primary Splenic Diffuse Large B-Cell Lymphoma Complicated by Gastrosplenic Fistula: A Case Report - Bibek Saha MD; Jenny J. Cao MBBCh; Zachary S. Kelm MD, PhD; Allison Reinhardt MD; Alex Danielson MD; Victoria Kalinoski-Dubose MD; William Mundell MD (Journal of Investigative Medicine High Impact Case Reports)
Diffuse large B-cell lymphoma (DLBCL) is the most prevalent and aggressive subtype of non-Hodgkin lymphoma comprising 30% to 40% of cases. While DLBCL frequently arises in the lymph nodes, up to 40% of cases originate in extranodal tissues. Primary splenic DLBCL is extremely rare comprising only ~1% of DLBCL cases and can be complicated by rare entities including gastrosplenic fistula (GSF). In contrast to DLBCL, polycythemia vera (PV) is a myeloproliferative malignancy. Polycythemia vera can transform into other hematologic malignancies including post-polycythemia myelofibrosis, but associations with DLBCL are uncommon. We present the first case of PV with concomitant primary splenic DLBCL complicated by GSF. While the majority of splenic lesions are benign, they have a broad differential diagnosis including malignant etiologies. Cystic or solid morphology, the number of lesions, and vascularity on imaging heavily guide further management. Due to concern for imminent massive upper gastrointestinal bleeding in the setting of GSF, our patient was diagnosed and managed with prompt splenectomy and gastrectomy. Percutaneous splenic biopsy is also a safe and effective diagnostic modality, but was deferred in our case given increased bleeding risk with PV. In conclusion, primary splenic lymphoma should be in the differential for a splenic mass regardless of whether the patient has a prior hematologic malignancy, and management should be prompt especially if complicated by a GSF.